2020
DOI: 10.1111/anu.13034
|View full text |Cite
|
Sign up to set email alerts
|

Lupin kernel meal as fishmeal replacement in formulated feeds for the Whiteleg Shrimp (Litopenaeus vannamei)

Abstract: Rapidly expanding global aquaculture requires sustainable, local protein sources to supplement the use of fishmeal. Lupin seed meal (Lupinus angustifolius) was tested as sustainable diet component for Whiteleg shrimp (Litopenaeus vannamei). Controlled feeding experiments were conducted in a recirculating aquaculture system for eight weeks. Juvenile shrimps were provided formulated diets containing various levels of lupin meal inclusion (0, 100, 200 and 300 g kg−1) supplementing the fishmeal component, and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…This is also in agreement with the previous work [22], where using the same diet formulation under controlled conditions, the shrimp did not show better FBW and biomass compared to the BD. Many studies have been conducted to replace FM with alternative ingredients or supplements in the development of practical diets for Pacific shrimp P. vannamei [25][26][27][28][29]. These authors concluded that the reduction of FM in diets will face two major issues: the reduction of the feed intake and the lower apparent digestibility of the alternative nutrients [30].…”
Section: Discussionmentioning
confidence: 99%
“…This is also in agreement with the previous work [22], where using the same diet formulation under controlled conditions, the shrimp did not show better FBW and biomass compared to the BD. Many studies have been conducted to replace FM with alternative ingredients or supplements in the development of practical diets for Pacific shrimp P. vannamei [25][26][27][28][29]. These authors concluded that the reduction of FM in diets will face two major issues: the reduction of the feed intake and the lower apparent digestibility of the alternative nutrients [30].…”
Section: Discussionmentioning
confidence: 99%
“…To meet the growing demands for shrimp feed, several researchers have examined the use of alternative protein sources in shrimp diet production. These researchers reported the successful use of ingredients originating from plant [8], animal [9,10] and microbial sources [11] as alternatives or complements of fishmeal in shrimp diets. Microbial protein is obtained from different microbial biomass sources such as yeast bacteria and microalgae, with great potential to partially or even completely replace fishmeal in shrimp diets [12].…”
Section: Introductionmentioning
confidence: 99%
“…This has led to restriction on the application of plant protein in aquafeeds. According to related studies conducted on high-level plant protein feed, Pacific white shrimp would perform reduced growth performance [11], body composition change [12], lowered digestion [13], and antioxidant obstacle [14]. In order to improve the utilization efficiency of plant protein, it is a question worth exploring that relieves the negative impact of fishmeal replacement [15].…”
Section: Introductionmentioning
confidence: 99%